2021
DOI: 10.14814/phy2.14707
|View full text |Cite
|
Sign up to set email alerts
|

17β‐estradiol reduces SARS‐CoV‐2 infection in vitro

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 31 publications
4
68
0
Order By: Relevance
“…As the sterols can potentially modify virus infection capacity, pretreatment with estrogen is likely to enhance protective actions in acute lung injury due to the anti-inflammatory effects. 63 A previous study suggested that estrogen could lower the activities of CMI, HI, and innate immune cells, like neutrophils and NK cells.…”
Section: Estrogenmentioning
confidence: 98%
“…As the sterols can potentially modify virus infection capacity, pretreatment with estrogen is likely to enhance protective actions in acute lung injury due to the anti-inflammatory effects. 63 A previous study suggested that estrogen could lower the activities of CMI, HI, and innate immune cells, like neutrophils and NK cells.…”
Section: Estrogenmentioning
confidence: 98%
“…We emphasize that we tested the effects of 4-OHT and fulvestrant at their therapeutic concentrations and demonstrated that they can signi cantly in uence the susceptibility of human ER expressing MCF7 cells to SARS-CoV-2 infection. Our results envision a therapeutic use of tamoxifen in infected people to restrain the severity of the symptoms, COVID-19 mortality and the vicious circle induced by SARS-CoV-2 infection on ACE2 and TMPRSS2 expression [47]. Potentially also a prophylactic use could reduce the risk of infection and spread of the disease.…”
Section: Discussionmentioning
confidence: 87%
“…These mechanisms were also dependent on the interaction of hormones with their receptors. The inhibitory effect of estrogens on replication was documented [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. in a panel of viruses (for particulars see Table 1 ).…”
Section: Effect Of Oestrogen Receptor Modulators (Erms) On Viral Replicationmentioning
confidence: 99%
“…Unfortunately, the precise molecular mechanisms of action were deciphered only in a few cases and are usually independent of the interaction with the receptor. Clomifene, raloxifene, ridaifene (+XL-147) and toremifene act via attenuation of the interaction of SARS−CoV−2 or EBOLA with their target cells [ 37 , 40 , 41 , 42 , 43 , 44 ], where some role of the inhibition of SARS−CoV−2 spike protein interaction with receptor ACE2 may be expected [ 36 , 37 , 39 , 44 , 45 , 67 ]. ERMs seem to inhibit the glycan–glycan interaction between the spike protein and ACE2 and so reduces the virus entry to permissive cells [ 43 , 68 ].…”
Section: Effect Of Oestrogen Receptor Modulators (Erms) On Viral Replicationmentioning
confidence: 99%